Adherence to Ethical Standards of Scientific Research and its Relation to Creativity in Educational Researches in the light of Some Demographic Variables: Exploratory Study - Arnaout, Bushra Ismail Ahmed (Journal of Educational and Psychological Sciences, 2019)
This study aimed to determine the level of adherence to the research ethical standards and research creativity in psychological and educational studies, and to identify the nature of the relationship between adherence to ethical standards and research creativity, as well as to identify the differences in both adherence to the research ethical standards and research creativity due to (gender, scientific degree, number of publications) variables. The researcher selected a random sample of (142) of the researchers in psychological and educational disciplines. There ages ranged between (26- 57) years. The researcher applied the scale of adherence to the research ethical standards and scale of research creativity, all of these tools prepared by the researcher. The results showed that there was a low level of adherence to the research ethical standards as well as low level of research creativity. Also there was a statistical significant strong positive correlation between adherence to research ethical standards and research creativity (R = 0.945), and also found statistically significant differences (0.01) among the average scores in adherence to the research adherence to ethical standards and research creativity due to gender (in favor of females), Scientific degree (in favor of doctoral and post-doctoral researchers), and the number of published researches (in favor of researchers who published more than 6 research and more who are publish more than Of 10 research). The results of the simple regression analysis also indicated that adherence to the research ethical standards is a statistical and powerful indicator of research creativity. The researcher explained the findings in light of the theoretical framework and previous studies, and developed a number of recommendations.